Asur Ticaret Kolonileri Çağı’nda (M.Ö. 1975-1723) Anadolu’da Hayvancılık ve Hayvan Ticareti - Gökçek, L. Gürkan
Animal Husbandry and Animal Trade in Anatolia during the Age of Assyrian Trade Colonies (1975-1723 B.C.)